2011
DOI: 10.1523/jneurosci.1245-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Bcl11b/Ctip2 Controls the Differentiation of Vomeronasal Sensory Neurons in Mice

Abstract: The transcription factor Bcl11b/Ctip2 plays critical roles in the development of several systems and organs, including the immune system, central nervous system, skin and teeth. Here, we show that Bcl11b/Ctip2 is highly expressed in the developing vomeronasal system in mice and is required for its proper development. Bcl11b/Ctip2 is expressed in post-mitotic vomeronasal sensory neurons (VSNs) in the vomeronasal epithelium as well as projection neurons and GABAergic interneurons in the accessory olfactory bulb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
101
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(114 citation statements)
references
References 53 publications
(70 reference statements)
10
101
0
Order By: Relevance
“…Disruption of the Bcl11b locus in mice results in defective neuronal (20,21), skin (22), craniofacial (23), and T-cell (20, 24 -26) development. Disruption of the human BCL11B locus has been associated with T-cell malignancies (27)(28)(29), suggesting that the protein acts as a tumor suppressor in T-cells (30).…”
mentioning
confidence: 99%
“…Disruption of the Bcl11b locus in mice results in defective neuronal (20,21), skin (22), craniofacial (23), and T-cell (20, 24 -26) development. Disruption of the human BCL11B locus has been associated with T-cell malignancies (27)(28)(29), suggesting that the protein acts as a tumor suppressor in T-cells (30).…”
mentioning
confidence: 99%
“…In a recent article published in The Journal of Neuroscience, however, Enomoto et al (2011) showed that Bcl11b/Ctip2, a zinc finger transcription factor involved in regulating corticofugal fate of deep-layered neocortical neurons , is crucial for maturation and fate determination of vomeronasal neurons, for establishing axonal projections to the AOB, and for correct layering of intrinsic AOB neurons.…”
mentioning
confidence: 99%
“…By analyzing gene expression at different developmental stages, Enomoto et al (2011) identify a sequence of events that occur during vomeronasal neuron maturation. They found that during embryogenesis, Bcl11b/Ctip2 is expressed in most terminal differentiating/immature vomeronasal neurons, whereas in adults, its expression becomes restricted to the neurogenic niches of the marginal regions of the VNO.…”
mentioning
confidence: 99%
See 2 more Smart Citations